Characterization of capacitive-type epidermal moisture measurements using disposable printed electrode films. (3rd August 2021) - Iwata, Shiro; Kusaka, Yasuyuki; Abe, Souichiro; Kato, Nobuyuki; Kanayama, Masahiro; Imawaka, Naoto; Ushijima, Hirobumi
Abstract: This paper addresses the characteristics of capacitive-type epidermal moisture measurements using disposable electrode films fabricated by a screen-printing method. The disposable electrode films were composed of substrates, comb-shaped electrode layers, and insulating layers. The epidermal moisture measurement obtained higher gain by optimization of the finger width of the comb-shaped electrode layer. The gain and accuracy of measurements were also improved by changing the insulating layer that covered the comb-shaped electrode layer to the striped-pattern type instead of the conventional solid-filling type. This epidermal moisture measuring instrument reduces the cleaning process of the electrode film that directly contacts the skin, simplifies the handling of the devices, and ensures hygienic operation.